Read-safe snapshots: An abort/wait-free serializable read method for read-only transactions on mixed OLTP/OLAP workloads - Shioi, Takamitsu; Kambayashi, Takashi; Arakawa, Suguru; Kurosawa, Ryoji; Hikida, Satoshi; Yokota, Haruo (Information systems (Oxford), 2024)
This paper proposes Read-Safe Snapshots (RSS), a concurrency control method that ensures reading the latest serializable version on multiversion concurrency control (MVCC) for read-only transactions without creating any serializability anomaly, thereby enhancing the transaction processing throughput under mixed workloads of online transactional processing (OLTP) and online analytical processing (OLAP). Ensuring serializability for data consistency between OLTP and OLAP is vital to prevent OLAP from obtaining nonserializable results. Existing serializability methods achieve this consistency by making OLTP or OLAP transactions aborts or waits, but these can lead to throughput degradation when implemented for large read sets in read-only OLAP transactions under mixed workloads of the recent real-time analysis applications. To deal with this problem, we present an RSS construction algorithm that does not affect the conventional OLTP performance and simultaneously avoids producing additional aborts and waits. Moreover, the RSS construction method can be easily applied to the read-only replica of a multinode system as well as a single-node system because no validation for serializability is required. Our experimental findings showed that RSS could prevent read-only OLAP transactions from creating anomaly cycles under a multinode environment of master-copy replication, which led to the achievement of serializability with the low overhead of about 15% compared to baseline OLTP/OLAP throughputs under snapshot isolation (SI). The OLTP throughput under our proposed method in a mixed OLTP/OLAP workload was about 45% better than SafeSnapshots, a serializable snapshot isolation (SSI) equipped with a read-only optimization method, and did not degrade the OLAP throughput.